2021
DOI: 10.3823/855
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance of Uropathogens at Governmental Hospitals in the Gaza Strip/Palestine

Abstract: Urinary tract infection is a public health problem worldwide. E. coli and klebsiella are among the main etiologic for UTI in Gaza Strip. The growing variations in resistance among uropathogens to antimicrobials is multifactorial and varies globally. It greatly reduces/limits or complicate treatment option. Aims: To determine the pattern of antimicrobial resistance and multidrug resistance among uropathogens at governmental hospitals. Methods: We analyzed the data of 11,890 urine samples processed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…55–57 The incidence rates of VRSA strains are diverse all over the world: 16% in Africa, 5% in Asia, and 1% in Europe, 4% in North America, and 3% in South America. 56 The VRSA in the current investigation is much lower related to reports from other countries. 23 , 58 …”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…55–57 The incidence rates of VRSA strains are diverse all over the world: 16% in Africa, 5% in Asia, and 1% in Europe, 4% in North America, and 3% in South America. 56 The VRSA in the current investigation is much lower related to reports from other countries. 23 , 58 …”
Section: Discussioncontrasting
confidence: 69%
“…54 It is clear that MRSA is a global health threat, as shown by the high rates of antimicrobial resistance reported in countries, such as Eritrea (72%), Turkey (21%), the Gaza Strip (82.3%), Iran (71.9%), and a tertiary care facility in Lahore (76%). [55][56][57] The incidence rates of VRSA strains are diverse all over the world: 16% in Africa, 5% in Asia, and 1% in Europe, 4% in North America, and 3% in South America. 56 The VRSA in the current investigation is much lower related to reports from other countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial resistance (AMR) is one of the leading public health concerns, especially in developing countries where a higher incidence of improper use of antimicrobial drugs and AMR exists [1]. Most antimicrobial drugs in developing countries, particularly in Gaza, are available to be given by the community pharmacist without a prescription and are subject to a lack of regulation [2]. An article in 2021 reviewed all studies published over a period of 20 years and reported widespread multi-drug resistance among bacterial pathogens recovered from clinical specimens and the hospital environment in the Gaza Strip, Palestine [3].…”
Section: Introductionmentioning
confidence: 99%